Breast Implant–Associated Anaplastic Large Cell Lymphoma: Report of 2 Cases and Review of the Literature. (August 2014) - Hart, Alexandra M.; Lechowicz, Mary Jo; Peters, Kendall K.; Holden, Jeannine; Carlson, Grant W.
Although primary breast lymphomas are exceedingly rare, cases of breast implant–associated anaplastic large cell lymphoma (iALCL) continue to be reported. The authors describe their experience with 2 patients and review the literature. Both patients presented with periprosthetic fluid collection. Neither had evidence of systemic disease nor received systemic therapy. Both were disease free after bilateral capsulectomies and implant removal without implant replacement, and disease did not recur. During the literature review, 63 cases of iALCL (including our 2 patients) were identified. The median time from implant placement to diagnosis was 9 years. Both saline and silicone implants were associated with iALCL. Of the 26 cases for which implant surface was reported, the surface was textured in 24. Of the 58 patients with an identifiable presentation, 39 had periprosthetic fluid collection, including 7 with an associated mass; 13 had an isolated mass at presentation, including 1 with axillary adenopathy. Forty patients had capsulectomy, 7 of whom underwent implant replacement. Of the 44 patients with known treatment, 33 received chemotherapy and 23 received radiation. Of the 49 patients with known anaplastic large cell lymphoma, 15 had disease recurrence, and 4 patient deaths were reported. Of the 18 patients presenting with a mass, 11 had disease recurrence, including all 4 patients who died. This study represents the largest review of patients with iALCL described to date. Although most cases have an indolent clinical course, the variety of presentations defined as "seroma" vs "capsular involvement" emphasizes the importance of investigating a definitive method of diagnosis, management, and treatment of this disease. Level of Evidence: 5